Advanced led selection and map detection in glim systems using fuzzy dynamic arithmetic optimization (FDAO) algorithm - Suresh, K.; Lathif, Syed Ismail Abdul; Jayasakthi Velmurugan, K.; Anand, Krishnamurthy (Optical and quantum electronics, 2023)
As emerging technologies, numerous studies were carried out based on multiple input multiple output (MIMO) visible light communication (VLC) system that includes both experimental and theoretical demonstrations. MIMO-VLC system significantly suffers from performance deficiency. Recently, Orthogonal Frequency division multiplexing is utilized for maintaining transmission rate and spectral efficiency. LED selection process plays a vital role in enhancing efficiency of generalized LED index modulation system with the adoption of MAP detection component that is greatly influenced by correlation among LED. Therefore, this paper designs a novel concept named fuzzy dynamic arithmetic optimization (FDAO) algorithm for the selection of optimal channel capacity. The proposed FDAO algorithm combines the mechanism of fuzzy logic system with the dynamic arithmetic optimization algorithm to select candidates with good channel capacity. FDAO algorithm automatically extracts and removes the candidate influenced by inaccurate active decisions and optimally selects the candidate solution with good channel capacity. Finally, the comparative analysis is carried out for diverse existing approaches with respect to bit error rate (BER) and index error rate (IER). The experimental analysis reveals that the proposed approach exhibited minimum BER and IER than other techniques.